Characterization of gallotannins from Astronium species by flow injection analysis-electrospray ionization-ion trap-tandem mass spectrometry and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - da Silva, Viviane Candida [UNESP]; Napolitano, Assunta; Eletto, Daniela; Rodrigues, Clenilson Martins [UNESP]; Pizza, Cosimo; Vilegas, Wagner [UNESP] (Im Publications, 2011)
The species Astronium urundeuva (Allemao) Engl. and Astronium graveolens Jacq., which are used in Brazilian folk medicine to treat allergies, inflammation, diarrhea and ulcers, were investigated for their composition. The aim of this study was to define a rapid and reliable analytical approach, based on the flow-injection analysis-electrospray ionization-ion trap-tandem mass spectrometry (FIA-ESI-IT-MS-MS) and matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-ToF-MS), to investigate the full range of hydrolyzable tannins present in the extracts of these Astronium species. The MALDI-ToF-MS analysis allowed us to ascertain the presence of hydrolysable tannins in both Astronium species as a series of gallotannins with degrees of polymerization of 7 to 13 galloyl units. Moreover, the analysis by FIA-ESI-IT-MS-MS, as well as confirming this result and chemically defining gallotannins as galloylglucose compounds, highlighted the presence of further classes of hydrolysable tannins, such as hexahydrodiphenoyl esters of glucose and some gallic acid derivatives, providing information about their structure by a careful study of their fragmentation patterns. Finally, the evaluation of the number of positional isomers of gallotannins occurring in both Astronium species was obtained by high-performance liquid chromatography-electrospray ionization-ion trap mass spectrometry (HPLC/ESI-IT-MS). This is the first mass spectrometric evidence relating to the existence of gallotannins in Astronium genus.
Keywords: Anacardiaceae; Astronium; gallotannins; MALDI-ToF-MS; FIA-ESI-IT-MS-MS